Bottom-up nationalism and discrimination on social media: An analysis of the citizenship debate about refugees in Turkey. (October 2020) - Bozdağ, Çiğdem
This study analyzes social media representations of refugees in Turkey and discusses their role in shaping public opinion. The influx of millions of Syrian refugees in Turkey has created heated debates about their presence and future in the country. One of these debates was triggered by President Erdoğan's statement that Turkey would issue citizenship rights to Syrians in July 2016. Due to a lack of critical voices about refugee issues in Turkey's mass media sphere, social media has become a key platform for citizens to voice their opinions. Through a discourse analysis of tweets about the issue of refugees' citizenship, I will map different perceptions of refugees in Turkey. I argue that despite contesting discourses about Syrians, the debate on social media reinforces nationalism and an ethnocentric understanding of citizenship in Turkey. As the number of refugees and migrants increases rapidly worldwide, they become the new 'others' of national imagined communities. Social media becomes a key communication space where the nation is discursively constructed in a bottom-up manner through manifestations of 'us' and 'them'. The analysis shows that social media contributes to trivialization and normalization of discrimination and hatred against Syrian refugees through disseminating overt discourses of 'Othering'. Social media also enables more covert forms of discrimination through 'rationalized' arguments that are used to justify discrimination through the basis of false/non-verified information. Thus, Twitter becomes a space for critical, bottom-up, yet nationalistic and discriminatory statements about refugees.